Comparative Effects of MMT Clay Modified with Two Different Cationic Surfactants on the Thermal and Rheological Properties of Polypropylene Nanocomposites - Meshal Al-Samhan; Jacob Samuel; Fatema Al-Attar; Gils Abraham (International Journal of Polymer Science)
Polypropylene montmorillonite (MMT) nanocomposites were prepared by melt blending using two different organoclays modified with imidazolium and alkylammonium surfactants. The imidazolium and ammonium modified organoclays were characterized by the FTIR and SEM analysis. The effect of organic clay (MMT) on the physical properties of polypropylene was evaluated, thermal and rheological properties with different filler weight percentage. Differential scanning calorimetric results showed that imidazolium modified clay (IMMT) exhibits low melting temperature compared to the ammonium modified clay (AMMT). The crystallinity analysis showed that crystallization improved in all nanocomposites irrespective of surface modification; the thermogravimetric analysis showed that the imidazolium modified polymer composites are more thermally stable than conventional ammonium modified composites. The Transmission Electron Microscopy (TEM) analyses indicated that the PP-IMMT composites displayed exfoliated morphologies compared with the intercalated structure in PP-AMMT, and the rheological analysis at 180°C showed an enhancement in the viscoelastic properties as the clay concentration increases. The melt viscosity, crossover modulus, and relaxation times were comparable for both the surface modified composites with two different cations. The imidazolium based surfactant was found to be an effective organic modification for MMT to prepare thermally stable PP/MMT nanocomposites.